Health Behavioral Changes of Patients with Uncontrolled Diabetes Mellitus by a Nutritional Surveillance and Resistance Exercise Program - Payuha, Pitakpong; Mongkonchoo, Nithima; Siwina, Satianpong (Journal of Preventive Medicine Association of Thailand, 2020)
This action research aimed to study health behavioral changes of patients with uncontrolled diabetes mellitus by a nutritional surveillance and resistance exercise program based on the concept of P (planning), A (acting), O (observing), and R (reflecting). The study population composed of adult participants who had 73 participants tested during study period, 30 uncontrolled Diabetes Mellitus Patients, 13 multidisciplinary team, and 30 village health volunteers. They were divided into 3 phases, plan, action evaluating and reflecting. Data were collected by using the test, practice of diabetic patients, question for interview, group discussion and participatory observation. They were performed from September 2018 to January 2020. Descriptive statistics were done using the number and percentage for categorical variables, mean ±SD, group compared using the paired t-test and the variables that presented a level of significance with a value of <.05 were considered statistically significant and theirs responding 95% confidence intervals (CI). Results: After development, diabetic patients who patients with uncontrolled diabetes mellitus had a lower waist than before development (p-value <.001), with a waist circumference reduced to 4.75 centimeters (95% CI: 3.17, 6.32), decreased body mass index (p-value = .019) with decreased body mass index 0.75 kilograms/square meter (95% CI; 0.42, 1.47) and HbA1c (Hemoglobin A1c) levels less than before development (p-value <.001) with decreased the HbA1c (Hemoglobin A1c) level equal to 0.54% (95% CI; 0.370, 0.709) Conclusions: In this study suggests, that the use of nutrition and resistance exercise as a result, uncontrolled diabetes mellitus patients had waist, body mass index and HbA1C (Hemoglobin A1C) can be reduced.